Effect of Deposited Sodium Stannite on the Flame Retardancy Imparted to Cotton Fabric - Morteza Mostashari, Seyed; Mahsa Golmirzadeh, Seyed (Asian Journal of Chemistry, 2016)
The effect of sodium stannite on the flammability of cotton fabric (Woven, 178 g/m2) has been of interest in this investigation. The aforementioned salt was synthesized by using suitable concentrations of NH4OH, NaOH and SnCl2 solutions. The optimum add-on values to impart flame-retardancy were about 5.9–6.5 g anhydrous sodium stannite per 100 g cotton fabric. The results obtained are in favour of the thermal theory. However, after the ignited specimens ceased to flame, the presence of glow was observed. Hence the condensed phase retardation cannot be justified.